2008
DOI: 10.1029/2007jd008653
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of organic trace gases including oxygenated volatile organic compounds at the high alpine site Jungfraujoch (Switzerland): Seasonal variation and source allocations

Abstract: [1] At the high alpine site Jungfraujoch (Switzerland) mixing ratios of 21 oxygenated volatile organic compounds (OVOCs) and selected nonmethane hydrocarbons (NMHCs) have been measured by a newly developed two-stage double adsorbent system coupled to a gas chromatograph-mass spectrometer (GC-MS). In addition, formaldehyde was measured by the Hantzsch technique. Four measurement campaigns were performed once every season in 2005, providing for the first time a unique data set of OVOCs in the free troposphere of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 50 publications
0
32
0
1
Order By: Relevance
“…The BASE simulation underestimates observed ethanol at all altitudes over North America and downwind of Asia by more than 50% and this underestimate worsens to over 100% over the remote southern Pacific. The BASE simulation also underestimates ethanol concentrations measured at the high alpine site Jungfraujoch (Switzerland) (Legreid et al, 2008) by over 100% (data not shown). As noted in the previous section, MOZART-4 adequately resolves boundary layer ventilation, therefore, this underestimate is unlikely to reflect a problem with the model vertical mixing.…”
Section: Resultsmentioning
confidence: 99%
“…The BASE simulation underestimates observed ethanol at all altitudes over North America and downwind of Asia by more than 50% and this underestimate worsens to over 100% over the remote southern Pacific. The BASE simulation also underestimates ethanol concentrations measured at the high alpine site Jungfraujoch (Switzerland) (Legreid et al, 2008) by over 100% (data not shown). As noted in the previous section, MOZART-4 adequately resolves boundary layer ventilation, therefore, this underestimate is unlikely to reflect a problem with the model vertical mixing.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an analysis of the seasonal variation of methanol in the lower troposphere and the UTLS has been performed, including comparisons with in situ measurements (Legreid et al, 2008) and to ACE-FTS occultation observations, respectively. Comparisons with simulations obtained from the IMAGESv2 global chemistry-transport model have also been conducted.…”
Section: Results and Comparisonsmentioning
confidence: 99%
“…al., 2006). Effects such as Foehn, deep convection, stratospheric intrusions, and synoptic lifting also influence receptor sites at high altitudes alternately and thus the transport of HCHO or its precursors to the sites (Zanis et al, 1999;Seibert et al, 2000;Balzani Lööv et al, 2008;Legreid et al, 2008). Effects of dilution and loss by deposition that can be particularly important for water-soluble HCHO also play an important role.…”
Section: Introductionmentioning
confidence: 99%